circRNA-UBAP2 promotes the proliferation and inhibits apoptosis of ovarian cancer though miR-382-5p/PRPF8 axis - Qin Xu; Bo Deng; Manlin Li; Yang Chen; Li Zhuan (BMC, 2020)
Abstract Objective circular RNAs (circRNAs) have been reported to be essential regulators of multiple malignant cancers. However, the functions of circRNAs in ovarian cancer need to be further explored. The aim of our study is to explore the role of circRNA-UBAP2 in ovarian cancer and its mechanism. Results circRNA-UBAP2 was upregulated in ovarian cancer tissues and cell lines. Knockdown of circRNA-UBAP2 inhibited cell proliferation and promoted cell apoptosis, but circRNA-UBAP2 overexpressed got opposite results. In addition, circRNA-UBAP2 targeted miR-382-5p and downregulated its expression, PRPF8 was a target gene of miR-382-5p. Furthemore, circRNA-UBAP2/miR-382-5p/PRPF8 axis affected the proliferation, apoptosis and cell cycle of ovarian cancer through the mechanism of competing endogenous RNAs (ceRNA). Conclusion circRNA-UBAP2 acted as a ceRNA to sponged miR-382-5p, increased the expression level of PRPF8, and prompted proliferation and inhibited apoptosis in ovarian cancer cells.